Function of Non-Judge Mediators in Divorce Settlement Through Religious Courts - Mardalena Hanifah; Meidana Pascadinianti (Universitas Negeri Semarang, 2023)
Marriage is carried out until the death of one of the husband and wife. In certain conditions, some things require the dissolution of a marriage, meaning that if the marriage relationship continues, harm will occur which will lead to divorce. Mediation as an out-of-court dispute resolution process is used by courts as a divorce settlement process. Mediation is carried out by a mediator, both a judge mediator and a non-judge mediator. The problem discussed is how to resolve divorce cases through mediation by non-judge mediators in the Religious Courts. The research method used is empirical research with qualitative analysis. Qualitative analysis is a study related to the integration of the substance of laws and regulations on divorce mediation and resolution in Religious Courts. Based on the results of research, the mediation process in the Religious Courts must be carried out by PERMA Number 1 of 2016 concerning Mediation Procedures in Courts, in line with islah as a peacemaker in Islam which has been carried out in the Religious Courts by mediator judges and non-judge mediators. The results of the study show that the success rate is very low. The cause of the failure of divorce settlement through mediation in the Religious Courts is the parties have the intention to divorce, making mediation only a requirement. In addition, the effectiveness of the mediator's function comes from the mediator's skills in handling divorce cases and the awareness of the parties to improve the household and the need for laws on mediation.